Is It Possible to Reduce the Relative Age Effect through an Intervention on Motor Competence in Preschool Children? - Marcos Mecías-Calvo; Víctor Arufe-Giráldez; Miguel Cons-Ferreiro; Rubén Navarro-Patón (MDPI AG, 2021)
The purpose of the study was to find out whether a short 6-week intervention on motor competence can reduce the Relative Age Effect (RAE) of preschool children born in the first quarter, compared to those born in the fourth quarter of the same year. Seventy-six preschool children (5.20 ± 0.54 years) from Lugo (Spain) participated. A quasi-experimental pre-post-test design was used with an intervention group (n = 32) and a control group (n = 44). The Movement Assessment Battery for Children-2 (MABC-2) was used to collect data before and after the intervention. The data show that, before the intervention, there are significant differences between the control and the intervention group in favor of the former (born in the first quarter of the year) in manual dexterity (p = 0.011), balance (p = 0.002), total test score (p = 0.008), and total percentile score (p = 0.010). After the application of the specific intervention, statistically significant differences were found in aiming and catching (p < 0.001), balance (p = 0.022), total test score (p = 0.001), and total percentile score (p < 0.001) in favor of the intervention group (born in the last quarter of the year). The results obtained suggest that the application of a specific intervention on MC could positively influence the improvement of MC in preschool children (boys and girls) and reduce the differences produced by the RAE.